Characteristics of Ice Cream with the Addition of Lactiplantibacillus plantarum SN13T Beads - Auliarasulina , Siti; Melia, Sri; Juliyarsi, Indri (Jurnal Ilmu dan Teknologi Hasil Ternak, 2025)
Ice cream is a dairy product that is loved by many people and has the potential to be developed as a functional food containing probiotics. This study aims to compare the quality of ice cream with the addition of encapsulated and non-encapsulated Lactiplantibacillus plantarum SN13T in ice cream products. The encapsulation technique was carried out using the extrusion method with alginate and starch coating materials, which were chosen for their ability to protect probiotic cells from extreme environmental conditions. The treatments in this study were Additions L. plantarum SN13T (A) and additions L. plantarum SN13T beads (B). The parameters measured were moisture content, protein, fat, pH, and total lactic acid bacteria. The data were then analyzed statistically using the T-test.  The results showed that the two methods did not show statistically significant differences (p > 0.05) in the chemical and microbiological parameters tested: water content, protein, fat, pH, and total colonies of lactic acid bacteria. This shows that ice cream, with the addition of L. plantarum with or without encapsulated beads, meets the quality requirements for ice cream and the requirements for probiotic food sources.